Hangry bees: Pollen dearth impacts honey bee (Apis mellifera) behavior and physiology - Elizabeth M. Walsh; Arián Avalos; Kate Ihle; Pierre Lau; Michael Simone-Finstrom; Anabelle A. Acosta; Mandy Frake; Sharon O’Brien; Giovanni Tundo (PLoS ONE, 2026)
Nutritional deprivation is known to contribute to increased honey bee mortality, physiological stress, aberrant behaviors, and disease incidence. To investigate the effect of a realistic nutritional protein deficiency, we simulated a pollen dearth in half of our experimental colonies by robbing incoming foragers of their pollen loads, the primary source of dietary protein, at the colony entrance. We then conducted temperament assays on each colony weekly for pollen deprived and control counterparts. We also identified the plant species bees foraged from and took various physiological measures of honey bee nutritional status including gland size, lipid quantification, and gene expression to further investigate and explain our behavioral results. We found that colonies deprived of pollen reacted by becoming more defensive and that immature bees likely receive cues during rearing which prime their gene expression and behavior as adults, ultimately suggesting that environmental stress caused significant behavioral changes. Temperament is primarily associated with genotype in the literature, but there are environmental cues that are less acknowledged and still important as our study shows. As droughts become increasingly frequent and resource availability therefore changes over time, the impacts on behaviors of agricultural keystone species need additional consideration in order to form scientifically driven best management practices.